Developing a safety and health program - Della-Giustina, Daniel (Boca Raton : CRC Press, 2010)
"Reflecting changes in the field during the ten years since the publication of the first edition, Developing a Safety and Health Program, Second Edition examines the elements of a safety and health program and delineates how to incorporate them into an organization's safety efforts. It begins by defining safety policy and providing an overview of OSHA and other regulatory agencies. It covers hazard communication safety training and describes how to write material safety data sheets, how to maintain a good fire loss control program, and procedures for developing an emergency response plan."--Book jacket.
ch. 1. Introduction -- ch. 2. Hazard communication and hazardous materials handling -- ch. 3. Job safety programs -- ch. 4. Accident and incident investigation -- ch. 5. Safety committees -- ch. 6. Fire loss control programs -- ch. 7. Emergency management and preparedness -- ch. 8. Logout/tagout -- ch. 9. Confined space entry -- ch. 10. Personal protective equipment -- ch. 11. Noise and ventilation -- ch. 12. Bloodborne pathogen standard.
Includes bibliographical references and index.
Also available in print format.
Mode of access: World Wide Web.
Keywords: Industrial safety -- Management; Industrial hygiene -- Management; Electronic books